Upaya Meningkatkan Aktivitas Peserta didik Kelas XI IPS 2 Pada Pembelajaran PAI Melalui Model Pembelajaran Discovery Learning di SMA Negeri 10 Padang - Idawarnis Idawarnis (Jurnal Kajian dan Pengembangan Umat, 2022)
One of the causes of low learning outcomes is the result of low student activity in learning and lack of interest and motivation of students to take lessons. For this reason, a solution is sought. Teachers conduct Class Action Research, one alternative solution is through a Discovery Learning model based on Guided Discovery, so from the description above I am as a pai teacher for class XI social studies 2 SMA Negeri 10 Padang. This study aims to increase student activity in PAI learning, so that finally it is expected to improve student learning outcomes. Improving student learning activities is carried out by applying the Discovery Learning model. This Class Action Research is carried out in two cycles. Each cycle consists of four meetings. In Cycle I, the Discovery Learning model is applied. The results of cycle I reflection are useful for improvement in cycle II. This can be seen from the data To see the comparison of the results of the PAI learning process with the teaching material of the Implementation of the Corpse which is carried out in each cycle Comparison between Cycles, that the comparison of student activities in each cycle has increased for the Activity category, (A1) it turns out that Discussing in groups working on LKS, it is stated that students from 50% increased to 66%, by 16% a lot of activities, (A2) it turns out that Doing LKS in accordance with the educator's instructions is marked by students raising their hands, it is stated that students from 46% have increased to 71%, by 25% have a lot of activities, (A3) it turns out that Asking educators is marked by students raising their hands, it is stated that students from 50% have increased to 81%, by 31% a lot of activities, (A4) it turns out that Answering educators' questions is characterized by raising their hands, stated students from 55% increased to 75%, by 20% a lot of activities, (A5) it turned out that expressing opinions was marked by raising their hands, it was stated that students from 63 increased to 82%, by 19% a lot of activities, (A6) it turned out that writing conclusions at the end of learning was marked by LKS evidence collected, it was stated that students from 72% increased to 88%, by 16% a lot of activities. Thus, the application of the Discovery Learning Learning Model based on Guided Discovery class XI social studies 2, can increase student learning activities in PAI Learning through Student Worksheets at SMA Negeri 10 Padang for the 2022/2023 Academic Year.